Literasi Keuangan Syariah untuk Generasi Milenial dalam Menggunakan Produk Keuangan Halal - Wahyuni Sirait; Siti Nur Rohmah; Intan Dinda; Meliyani Meliyani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Sharia financial literacy plays a crucial role in shaping the financial behavior of millennials, especially in selecting halal financial products. Amid the rapid growth of the Islamic finance industry, a clear understanding of fundamental concepts such as contracts (akad), usury (riba), and halal-haram distinctions is essential. This study aims to explore the level of sharia financial literacy among millennials and its influence on their preference for halal financial services. Using a qualitative method with literature study and observation, this research investigates patterns and awareness in financial decision-making. The findings indicate that higher literacy levels correlate positively with the use of sharia-compliant products, showing that informed millennials are more likely to support ethical and syariah-based financial systems. The study concludes that enhancing financial literacy can strengthen the role of millennials in developing a sustainable Islamic economic ecosystem in Indonesia.